Acorus calamus Exhibiting Antidiabetic Activity: An in vitro and in silico Approach - Samajdar, Saptarshi (Asian Journal of Biological and Life Sciences)
Background: Diabetes mellitus is a multifaceted metabolic disorder characterized by chronically elevated blood glucose levels. Existing therapeutic strategies often present limitations such as adverse toxicity and the emergence of drug resistance, necessitating the search for safer and more effective alternatives. Aim and Objectives: The present study aimed to evaluate the antidiabetic potential of natural compounds derived from Acorus calamus through in vitro α-amylase inhibition and in silico molecular docking approaches targeting key diabetic protein receptors. Materials and Methods: A total of 12 natural compounds extracted from Acorus calamus were subjected to α-amylase inhibition assays to assess their in vitro antidiabetic activity. Additionally, molecular docking studies were performed using AutoDock Vina against two key protein targets, PDB IDs: 1XU7 and 3C45. Toxicity prediction, drug-likeness, and pharmacokinetic properties were analyzed using SwissADME and ProTox-II platforms. Molecular dynamics simulations were conducted using the iMODS server. Results: The Acorus calamus extract demonstrated a superior α-amylase inhibitory activity with an IC₅₀ value of 2.87±0.38 mg/mL, outperforming the standard drug metformin (3.25±0.47 mg/mL). Among the 12 tested compounds, Galgravin exhibited the highest binding affinities for both 1XU7 (-8.5 kcal/mol) and 3C45 (-7.7 kcal/mol), surpassing those of metformin (-7.3 kcal/mol and -6.7 kcal/mol, respectively). Galgravin also showed the lowest predicted toxicity, highest LD₅₀ values, favorable drug-likeness, and excellent bioavailability. Molecular dynamics studies further confirmed its stable interaction and favorable dynamic behavior. Conclusion: The findings highlight Galgravin, a compound from Acorus calamus, as a promising natural inhibitor of key diabetic targets, potentially surpassing metformin in efficacy and safety. These results advocate further in vivo and clinical evaluations to validate its therapeutic potential in diabetes management.
Keywords: α-Amylase assay; Molecular Docking; ADME Studies; Toxicity Prediction; Molecular Dynamics.